Analisis Hasil Supervisi Akademik Kepala Madrasah Dalam Meningkatkan Profesionalisme Guru MTS Negeri 2 Kotawaringin Barat: Analysis Of The Results Of Academic Supervision By The Principal Of Madrasah In Improving The Professionalism Of Teachers At MTS Negeri 2 Kotawaringin Barat - Kartini, Nurul Hikmah; Suratno, Suratno; Fatchurahman, M. (Anterior Jurnal, 2026)
This study aims to describe and analyze the outcomes of the principal’s supervision in improving teacher professionalism at MTs Negeri 2 Kotawaringin Barat. The research focuses on the supervision practices implemented and their impact on the development of teacher competencies. A qualitative approach with a case study method was employed, and data were collected through participatory observations, in-depth interviews with the vice principal for curriculum affairs and teachers, as well as documentation related to supervision programs and their results. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing supported by continuous verification. The findings reveal that the supervision conducted by the principal at MTs Negeri 2 Kotawaringin Barat has successfully enhanced teachers’ pedagogical, professional, social, and personal competencies. The strategies applied include scheduled classroom supervision planning, individualized guidance, teacher performance evaluation, and needs-based training and workshops. Supporting factors consist of the principal’s strong commitment, a collaborative work culture, and adequate facility support, while the main obstacle lies in limited supervision time. The study indicates that the effectiveness of supervision outcomes is strongly influenced by teachers’ readiness to receive feedback and their willingness to improve themselves, along with supportive policy direction from the principal. These findings align with the concept of supervision that emphasizes improving the quality of learning and highlight its important role in promoting teacher development. The study recommends strengthening teachers’ capacity as learning practitioners through training in developing digital instructional media and enhancing interpersonal communication skills. Thus, the outcomes of the principal’s supervision can improve teacher professionalism and ultimately contribute to the sustainable improvement of education quality in the madrasah.